A Endogamia em redes mercantis da ‘Primeira Idade Global’. O caso da rede de Simon Ruiz (1553-1597) - Ribeiro, Ana Sofia (Faculdade de Letras da Universidade do Porto, 2012)
In historiographic narratives, Early Modern trading networks are claimed to promote endogamic strategies for selecting business agents in distant places, as well as for matrimonial and economic partnerships. Focusing on Simon Ruiz trading and financial company (1558-1597) as a case study, this paper questions this theoretical assumption of Early Modern historiography. Through network analysis, it shows the limited degree to which endogamy based on kinship, confessional compatibility, and on a common geographic provenience functioned as a way to entangle and strengthen trade and finance and as a strategy for network expansion and increasing business profits. The selected data sources for this purpose were the documents produced by Simon Ruiz and his company, namely bills of exchange and commercial correspondence.
Keywords: endogamia; redes mercantis; família; comércio inter-cultural; cooperação